Impact of dietitian delivered intensive nutrition intervention on dietary intake and weight outcome among gynecology cancer outpatient prior to surgery - Mohammad, Aini Masitah; Abu Zaid, Zalina; Ho, Chiou Yi; Ibrahim, Zuriati; Mat Daud, Zulfitri ‘Azuan; Md. Yusop, Nor Baizura; Jamhuri, Norshariza; Mohd Samwil, Siti Nuraini; Abdul Rahman, Zuwariah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: This is open label randomised control trial, aimed to identify whether an early (commenced at the time of diagnosis) and intensive nutrition intervention (INI) (individualised dietary counselling, oral nutritional supplements [ONS], telephone, and home visit) can improve weight and dietary intake of gynaecological cancer (GC) patients preoperatively. Methods: Selected GC patients planned for surgery were randomly grouped into control group (CG) (n = 35) and intervention group (IG) (n = 34). Malnutrition screening tool (MST) was used as a screening tool, while Patient-Generated Subjective Global Assessment (PG-SGA) was used as a nutrition assessment tool. IG received an intensive individualised dietary counselling with the supply of ONS at baseline (Day 1). This continued with telephone and home visit follow-up by research dietitian (Day 3 and Day 6). Meanwhile, CG only received general nutritional counselling without supply of ONS. Final assessment was conducted on Day 14. The primary outcomes included weight changes measured using TANITA and dietary intake assessment using 24-hour diet recall. Results: Mean duration of INI was 14 days. At the end of the treatment period, there was a significant weight change between groups (p < 0.001), with 0.14% weight gain in IG and 1.3% weight reduction in CG. Mean energy and protein intake of IG were higher compared to CG by +329 kcal/day and +12.2 g/day, respectively. Conclusion: This study showed that INI that incorporated individualised dietary counselling, ONS, telephone counselling, and home visit can increase energy and protein intake of GC patients, resulting in weight gain.